SUBSTITUTION OF FISH OIL WITH PALM KERNEL OIL IN DIETS OF Oreochromis niloticus FRY: EFFECTS ON GROWTH, FEED UTILIZATION AND ECONOMIC ESTIMATES - Christian Larbi Ayisi; Elliot Haruna Alhassan; Freda Sarfo (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2021)
This study assessed the impact of replacing fish oil with palm kernel oil (PKO) in the diet of Oreochromis niloticus fry on growth, feed efficiency and proximate composition. Three isonitrogenous (30% crude protein) and isolipidic (10% crude lipid) diets were formulated using palm kernel oil as a substitute for fish oil at 0% (PKO-0), 50% (PKO-50), and 100% (PKO-100). Two hundred O. niloticus fry with initial weight of 0.80± 0.25g were purchased from Water Research Institute Upper West, Ghana and transported to the Spanish Laboratory of University for Development Studies (Ghana) where they were kept and fed two times a day on commercial diet from Ranaan feed for two weeks. The fry was then stocked in triplicate groups in 60 L tanks (50 cm x 40 cm x 40 cm) at 20 fry per tank. At the end of the eight weeks feeding trial, there was a significant difference amongst the three treatments with respect to final weight, weight gain, feed conversion ratio, and specific growth rate. It was observed that the least mean values for feed intake, protein productive value, protein efficiency ratio, and protein intake occurred in fish fed PKO-0. There was a trend of increasing whole body moisture content as palm kernel oil increased. Fish fed PKO-0 recorded the lowest lipid content (7.48 ± 1.13%) in the whole body. From the economic analysis, it is evident that palm kernel oil is a cheaper source of lipid for tilapia. This study therefore recommends palm kernel oil as a substitute for tilapia diet.